The Effectiveness of an E-Module Based on Socio-Scientific Issues to Improve Critical Thinking - Amalia, Gina; Ellianawati, Ellianawati; Siti Alimah (Universitas Negeri Semarang, 2024)
Technology in the era of the fourth industrial revolution is a trend that cannot be avoided and teachers are required to integrate the learning process with existing technology. However, this has not been implemented in many schools so students tend to be passive during learning. In learning, technology integration plays a role in increasing student motivation. Through a socio-scientific issues approach with problem-based learning syntax, students can develop problem-solving skills that are relevant to the real world. This research aims to measurement an e-module based on Socio-Scientific Issues with a Problem-Based Learning (PBL) model on the ecosystem concept to improve critical thinking. The type of research chosen is the research design used a pretest-posttest control group design. Based on the research results, the effectiveness test, it can be seen that the SSI-based e-module can improve students’ critical thinking skills, especially in the aspects of concluding as well as conjecture and integration where the N-Gain value is >0.7 in the high category.